FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU IBU NIFAS DALAM PEMBERIAN KOLOSTRUM DI WILAYAH KOTATIP CILACAP - Savitri, Naomi Parmila Hesti; Oktaviana, Anisa Sevi (Universitas Harapan Bangsa Purwokerto, 2021)
Colostrum is the first milk composition that contains antibodies that are useful for immunity newborns up to 6 months. Incidence of malnutrition that causes growth disorders in infants due to lack of a history of giving colostrum during the newborn. This study was to determine the factors that influence the behavior of postpartum mothers in the delivery of colostrum. The research method is analytical observation to explain the factors that influence the behavior of postpartum mothers in the delivery of postpartum maternal colostrum at 36 kotatip Cilacap region selected using area proportional random sampling technique. The data analysis using chi quadrat. The results showed that there is a significant influence of factors on the behavior of parents experience postpartum mothers to give colostrum (p <0.01), factors influencing the behavior of family knowledge postpartum mothers to not give colostrum (p <0.01), health workers support factor give a significant influence on the behavior of postpartum mothers to not give colostrum (p <0.01), and pregnancy planning factors influence the behavior of postpartum mothers to give colostrum (p <0.01). While the mother's knowledge factors and economic status did not significantly affect the behavior of postpartum mothers to give kolsotrum (p> 0.01). Conclusion of this research is that there is significant influence of parental experience, knowledge of the family, the support of health professionals and planning a pregnancy to behavior of postpartum mothers to give colostrum. There is no significant effect of mother's knowledge and economic status on the behavior of postpartum mothers to give colostrum.